Remarks on the Roman Bridge over the Lavella River, along the Herculia Route in Hirpinia - Guacci, Paola (Eikón / Imago, 2021)
This paper aims to present the unpublished remains of a bridge, located in Irpinia (northeastern Campania, Italy) and pertinent to the via Herculia. In particular, some surveys and aerotopographical data acquired in these years let to reconstruct the irpinian “via Herculia” path, in the area of Ariano Irpino modern city. The topographical reconstruction of the route, referred to tetrarchic period, has been based on some published milestones and other archeological evidences, such as rural settlements. Recently, the discovery of a bridge over the Lavella River, in Ariano Irpino territory, allow to add a new contribute to the topographical research.